The Australia and New Zealand Cardio‐Oncology Registry: evaluation of chemotherapy‐related cardiotoxicity in a national cohort of paediatric cancer patients. Issue 2 (25th February 2021) - Lapirow, Daniel; La Gerche, Andre; Toro, Claudia; Masango, Emma; Costello, Ben; Porello, Enzo; Ludlow, Louise; Marshall, Glenn; Trahair, Toby; Mateos, Marion; Lewin, Jeremy; Byrne, Jennifer; et al.
Abstract: Cancer therapy related cardiac dysfunction (CTRCD) is an area of increasing focus, particularly during the survivorship period, for paediatric, adolescent and adult cancer survivors. With the advent of immunotherapy and targeted therapy, there is a new set of mechanisms from which paediatric and young adult patients with cancer may suffer cardiovascular injury. Furthermore, cardiovascular disease is the leading cause of morbidity and mortality in the survivorship period. The recently established Australian Cardio‐Oncology Registry is the largest and only population‐based cardiotoxicity database of paediatric and adolescent and young adult oncology patients in the world, and the first paediatric registry that will document cardiotoxicity caused by chemotherapy and novel targeted therapies using a prospective approach. The database is designed for comprehensive data collection and evaluation of the Australian practice in terms of diagnosis and management of CTRCD. Using the Australian Cardio‐Oncology Registry critical clinical information will be collected regarding predisposing factors for the development of CTRCD, the rate of subclinical left ventricular dysfunction and transition to overt heart failure, further research into protectant molecules against cardiac dysfunction and aid in the discovery of which genetic variants predispose to CTRCD. A health economic arm of the study will assess the cost/benefit of both the registry and cardio‐oncology clinical implementation. Finally, an imaging arm will establish if exercise cardiac magnetic resonance imaging and VO2 max testing is a more sensitive predictor of cardiac reserve in paediatric and adolescent and young adult oncology patients exposed to cardiac toxic therapies.